A MIXED-METHOD STUDY ON PREVALENCE OF SPECIFIC LEARNING DIFFICULTIES IN SLOW LEARNERS AND ITS IMPLICATIONS FOR ACADEMIC ACHIEVEMENTS - Faisal Naeem Khan; Samoona Kousar; Dr Rukhsana Bashir (International Journal of Contemporary Issues in Social Sciences, 2024)
Specific learning difficulties (SLDs) were the invisible cause of dropout from general education classroom because such students are not identified and suffer from pedagogical competence in general education classroom which affects the progress of these students badly. The present study aimed to investigate the prevalence of SLDs in slow learners and also brought to light on awareness and knowledge of a teacher in slow learner schools. The referral process of slow learner from regular to special centers has been explored as well. Mixed-method exploratory design was used to find out the prevalence of the students with SLDs and its implication in academic achievements in slow learner students. A data of 400 slow learner’s students, 10 teachers of slow learners and 5 regular teachers was collected using purposive sampling technique. The quantitative data was analyzed by SPSS and for qualitative, thematic analysis was used. The mean analysis revealed that majority of slow learners have writing difficulties (M=18.6) followed by reading difficulties (M=17.9) and mathematical difficulties (M=7.3). The qualitative findings revealed that no assessment process was followed in slow learner schools to identify the SLDs. Mostly teachers were unaware and had no pedagogical competencies to identify and compensate the slow learner students. The study found that lack of teachers’ training about SLDs and policy restrictions in general education was the biggest hurdle for referral process. Special trainings required for special education and general education teachers to improve the pedagogical competencies and classroom practices to handle the slow learner students. The hurdles in policy for the referral process and evaluation process must be encountered.